Jack Whitten - cosmic soul - Shiff, Richard 1943- (Hauser & Wirth Publishers, 2022)
This comprehensive monograph surveys the work of Black American artist Jack Whitten, known for his swirling, mosaic-like abstractions and his innovative material experimentations, especially with acrylic paint. Resembling topographical maps, Whitten's works rely heavily on the use of geometry and rhythmic, gestural structures to induce an artistic and spiritual process that he identifies as "mapping the soul". Focusing on pivotal developments over his six-decade career, the publication is generously illustrated with Whitten's vast body of work. Throughout the volume, art historian Richard Shiff provides critical interpretations of Whitten's painting, sculpture and artistic philosophy. Exhibition: Hauser & Wirth, Zurich, Switzerland (10.06. - 29.07.2022)
Exhibition. - Ausstellungsdaten ermittelt 10.06. - 29.07.2022 in Zürich
Keywords: Whitten, Jack -- 1939-2018; Bildband; Ausstellungskatalog -- 10.06.2022-29.07.2022 -- Zürich